A two phase energy-efficient routing protocol for underwater wireless sensor network to enhance data gathering. (2019) - Prathiba, R.; Nagarajan, G.
Underwater sensor network (UWSNs) characteristics such as low bandwidth, long propagation delay, limited energy, node mobility and error rate are bring many challenges in designing routing. UWSNs consist of high density sensor nodes deployed underwater to perform collaborative monitoring and resource exploration tasks over given area. The nodes in network are participates a specific task like sensing and forwarding the information to other nodes using routing protocols. Energy efficiency becomes the basic need of UWSNs in very deep water level condition and the main aim is to operate sensor with smaller battery for a longer time. In this paper, we propose an energy efficient routing protocol for UWSNs using two phase process (EERP-TP). Firstly, the balanced collective region is formed by conditional Sierpinski triangle algorithm using the node constraints, which improves the effectiveness of data gathering. Secondly, the candidate set selection is performed by chaotic multi-criteria decision (CMD) model, which computes best data forwarding node to deliver data to the destination within the required time. The simulation results show that the proposed EERP-TP method can perform very efficient than existing routing in terms of network lifetime, throughput, packet relayed rate, data loss, and energy consumption.